Assessing The Role of Water-Related Regulations and Actors in The Operation of PDAM (Local Drinking Water Company) - Fransiska, Fransiska (The Indonesian Journal of Planning and Development, 2022)
Water management in Indonesia has not been addressing water problems and challenges needed in achieving SDG 6, especially in the provision of sustainable drinking water services. Based on the condition, this research starts with a hypothesis that current performance of PDAM (Perusahaan Daerah Air Minum – Local Drinking Water Companies) – that have significant roles in drinking water provision in Indonesia regions – is influenced by water-related regulations and actors. With the aim to analyse the influence of regulations and actors related to the operation of PDAM, and to formulate recommendations that helps better PDAM performance in providing sustainable drinking water services, this study analyses regulations underlying PDAM governance and performance. Using content analysis on regulations, reports, and documents related to PDAM, this research has figured out that the operation of PDAM has not been supported with effective regulations, which is exacerbated by poor implementation and low enforcement of the regulations at the operational level by determined parties: local governments and PDAM. Therefore, to improve PDAM performance, this study recommends the Government of Indonesia to integrate and simplify PDAM-related regulations to avoid overlapping regulations and regulatory obesity and to review, analyse, state and disseminate clearly the status of existing PDAM-related regulations in the hierarchy of repealed and ineffective regulations to avoid confusion, stagnation and wrong decision making in the operation of PDAM. This study also finds out that further research on internal and external factors of water utilities (environment, biology, water and human resources, public policy, public services etc.) is necessary for sustainable provision of drinking water services and water security purposes and to ensure that the use or the implementation of those factors be clearly regulated.